2002
DOI: 10.1177/147309520200100104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Plans Pragmatically

Abstract: In this article I take up the topic of plan evaluation. I compare two approaches. One approach uses Rational analysis, the other pragmatic reasoning. I argue that planners should place less emphasis on rational analysis and adopt a distinctly pragmatic approach when evaluating plans. Analysis may offer objectivity and precision, but it sacrifices context and continuity. A pragmatic outlook embraces context and seeks continuity among diverse viewpoints. It avoids the separation between analysis and action, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 18 publications
(15 reference statements)
0
28
0
Order By: Relevance
“…(h) To promote the environmental compensation principle in sensitive areas, whenever it translates into services provided by nature conservation selecting outcomes/effects indicators was high, given that a considerable part of the outcomes expected by PROT Algarve are not a direct and immediate result of plan implementation. This was anticipated from the beginning, considering the strategic nature of PROT Algarve, and constitutes one of the difficulties identified in previous works (Therivel et al, 1992;Arts, 1998;Hoch, 2002;Partidário and Arts, 2005). Therefore, only the objectives that the plan identifies in a clear and concise manner were considered to derive indicators (although other objectives could be deduced by interpreting the plan's contents).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(h) To promote the environmental compensation principle in sensitive areas, whenever it translates into services provided by nature conservation selecting outcomes/effects indicators was high, given that a considerable part of the outcomes expected by PROT Algarve are not a direct and immediate result of plan implementation. This was anticipated from the beginning, considering the strategic nature of PROT Algarve, and constitutes one of the difficulties identified in previous works (Therivel et al, 1992;Arts, 1998;Hoch, 2002;Partidário and Arts, 2005). Therefore, only the objectives that the plan identifies in a clear and concise manner were considered to derive indicators (although other objectives could be deduced by interpreting the plan's contents).…”
Section: Resultsmentioning
confidence: 99%
“…Chaker et al (2006) have reviewed SEA systems in twelve countries and observed that only in Denmark, the Netherlands and the United Kingdom were there requirements for monitoring (this applies to all spatial scales, not only regional). Arts (1998), Hoch (2002 and Partidário and Arts (2005) have identified several problems inherent in the monitoring process that help explain the above observations, including: (i) the selection of relevant indicators; (ii) data gathering; (iii) lack of resources in terms of time and money; (iv) the level of abstraction at strategic level; (v) uncertainties; and (vi) the establishment of causal relationships between strategic plans and corresponding impacts. This last problem is highlighted by Therivel et al (1992) on the regional scale, as an observed effect may come from other adjacent or distant regions.…”
Section: Monitoring Of Regional Spatial Plansmentioning
confidence: 99%
“…Finally, a key function of strategic planning efforts is to figure out where and how best to lodge the function within an enterprise. The functions of implementation also encompass strategic thinking, acting, and learning, but with more of a pronounced emphasis on ongoing learning‐by‐doing in a very pragmatic way within the constraints (which may be questioned) of established mandates, mission, goals, and strategies (Dewey 1954; Hoch 2002, 2007; Simons 1995). Action learning (Eden and Huxham 2006) and organization development (Cummings and Worley 2008) are thus important parts of both strategic planning and implementation, including learning focused on developing the strategic management system so real public value is created and sustained over time.…”
Section: Strategic Planning and Strategic Management: Definitions Fumentioning
confidence: 99%
“…Frequently these relate to stakeholder participation in planning and implementation, a fundamental premise of modern integrated marine management [29]. Hoch goes as far as to suggest that participation in a planning process by itself might changes peoples' lives, cautioning though that some of these changes might not be perceived as such, let alone attributable to that participation [30].…”
Section: Timing and Scopementioning
confidence: 99%